EVALUASI MANAJEMEN KEARSIPAN DI BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA (BKPSDM) KABUPATEN LAMPUNG TENGAH - Eko Mei Susanto (SEMINAR NASIONAL PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT, 2022)
This study aims to determine and explain how records management in the Civil Service and Human Resources Development Agency (BKPSDM), Central Lampung. This research was conducted at the Personnel and Human Resources Development Agency (BKPSDM) Central Lampung with a total of 10 respondents. Data analysis in qualitative research consists of several activity lines, namely data reduction, data presentation, data verification and conclusion drawing. 1). The creation of archives still encountered obstacles in recording / registering. 2). The procedure for managing records in this office has not been going well, this is evident from the accuracy and length of time to recover archives of more than one minute. 3). Archive storage system is still very simple. 4). Arrangement and transfer of archives that are not in accordance with archiving guidelines. 5). Human resources are still lacking as well as knowledge and understanding of archive management. 6). The archive retention schedule is not scheduled or almost non-existent. 7). Archive maintenance is very lacking, archives look dusty, folded, not maintained and not a few are damaged.